National Dam Inspection Program. Analomink Lake Dam (NDI ID PA 00638, PA DER Number 45-32), Delaware River Basin, Unnamed Tributary of Brodhead Creek, Pennsylvania. Phase I Inspection Report - Williams, John J. (1981)
Analomink Lake Dam is an 11-foot high, 280-foot long rock fill and earth embankment, built approximately 70 years ago to provide an impoundment for recreational purposes. The dam has an average crest width of eight feet and a downstream slope which varies from 1H:1V to nearly vertical. The upstream face of the dam is almost completely submerged, but it is believed to have a much flatter slope than the downstream face. The Spillway is classified as Inadequate. Based upon the inspection of the dam and review of the information provided by the Pennsylvania Department of Environmental Resources (DER), Analomink Lake Dam is considered to be in poor condition. Original contains color plates: All DTIC and NTIS reproductions will be in black and white